Frequency-selective propagation of localized spoof surface plasmons in a graded plasmonic resonator chain - Gao, Zhen (2017)
Localized spoof surface plasmon polaritons (spoof-SPPs) in a graded spoof-plasmonic resonator chain with linearly increasing spacing are experimentally investigated at microwave frequencies. Transmission measurements and direct near-field mappings on this graded chain show that the propagation of localized spoof-SPPs can be cutoff at different positions along the graded chain under different frequencies due to the graded coupling between adjacent resonators. This mechanism can be used to guide localized spoof-SPPs in the graded chain to specific positions depending on the frequency and thereby implement a device that can work as a selective switch in integrated plasmonic circuits.